Case 3744: Bidessus Sharp, 1880 (Coleoptera, Dytiscidae, Bidessini): proposed conservation of usage by designation of Dytiscus unistriatus Goeze, 1777 as the type species - Bousquet, Yves; Bouchard, Patrice (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Articles 70.2 and 81.1 of the Code, is to preserve stability in the taxonomy of the beetle family Dytiscidae by designating Dytiscus unistriatus Goeze, 1777 as the type species of Bidessus Sharp, 1880. The discovery of an earlier use of the name Bidessus, previously attributed to Sharp in 1882, with Dytiscus geminus Fabricius, 1792 as type species, results in disruptive nomenclatural changes in the family Dytiscidae if accepted.
Keywords: Nomenclature; taxonomy; Coleoptera; DYTISCIDAE; BIDESSINI; Dytiscus unistriatus; Dytiscus geminus; type species